The Subaltern Speaks in Anna Weamys’ A Continuation of Sir Philip Sidney’s Arcadia: A Foucauldian Perspective - Merve Aydoğdu Çelik (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
This paper examines how the servant Mopsa in Anna Weamys’ A Continuation of Sir Philip Sidney’s Arcadia provides a negative answer to Gayatri Chakravorty Spivak’s question whether the subaltern can speak. In accordance with Michel Foucault’s thoughts on power and resistance, it intends to reveal that the subaltern, contrary to what Spivak proposes, is able to raise voice and demonstrate resistance. Mopsa has not been given the chance to speak among the royals in Sir Philip Sidney’s The Countess of Pembroke’s Arcadia, but Weamys deconstructs Sidney’s version and provides Mopsa the opportunity to transcend subalternity as she asserts her action and voice. Within this framework, Anna Weamys’ romance can be read, in the context of Foucault’s theory on power, as a challenge against Spivak’s assumption which contends that the subaltern is not recognizable.